Comparative Study Of The Laskar Pelangi Novel With The Dua Belas Pasang Mata Novel Reviewed From Structural Approach - Aulia Putri Gustri Rusmi (Universitas Veteran Bangun Nusantara, 2022)
The goal of this research is to compare the Laskar Pelangi novel to the Dua Belas Pasang Mata novel in order to establish the narrative's building elements. This study employed the descriptive research method. The author describes the data obtained in a systematic, factual, and correct manner in order to discover facts and causative processes. The data is in the form of recorded documents that describe the structure of the novel using literary analysis. As a result of this inquiry, Andrea Hirata's novel Laskar Pelangi contains 48 chapters and diverse themes that will be transferred. The key plot elements of this work are as follows: The story begins with the registration of students at a Muhammadiyah elementary school in Gantong village, Gantong sub-district, East Belitong, South Sumatra. To better comprehend the arrangement, there will be three steps: establishing the area, the period, and the community from the start to the last chapter, the action of this novel takes place in Belitong. This novel is set in several locales across Belitong. This novel uses the viewpoint as the primary character based on the role. Furthermore, the central theme of the novel Dua Belas Pasang Mata is the main character's sympathy and affection. Starting with a story about Miss Oishi's first visit to Tanjung village as a substitute teacher at a branch school and the reaction of the local people to her wearing western attire at the time. Thus, it is known that both novels have extraordinary social crisis stories.